Mental health and life satisfaction among those advised to shield during the COVID-19 pandemic in the UK: a secondary analysis of the Understanding Society longitudinal study - Morris, Simon George; Kudrna, Laura; Martin, James (Frontiers in Public Health, 2023)
Introduction During the COVID-19 pandemic in the UK, those considered most vulnerable to adverse outcomes from infection were designated “clinically extremely vulnerable” and advised to “shield.” This involved prolonged confinement at home with strict limits on face-to-face contact, beyond national restrictions. Shielding ended in September 2021 and was considered likely to have harmed mental health and wellbeing. As the UK moved toward a new phase of “living with COVID-19” the mental health and wellbeing experiences of those advised to shield may have diverged from the general population. Methods This study is a secondary analysis of nine “COVID-19 Survey” waves of Understanding Society, a longitudinal study of UK participants covering April 2020 to September 2021 alongside pre-pandemic baseline data. The prevalence of clinically significant psychological distress (General Health Questionnaire 12) and low life satisfaction were examined at each wave for participants with longitudinal responses across all waves, stratified by receipt of shielding guidance (Received n = 410, Not received n = 6,878). Mixed effects regression modeling examined associations between shielding guidance receipt and mental health and life satisfaction when adjusting for potential confounders including age and sex, pre-pandemic mental health/life satisfaction, and loneliness. Results Those who received shielding guidance were more likely to experience poor mental health and low life satisfaction during the pandemic. However, this largely reflected differences in pre-pandemic baselines. Variation between waves broadly coincided with the changing burden of COVID-19 and associated restrictions, with similar patterns regardless of shielding guidance receipt. Regression modeling combining data across all waves indicated that receipt of shielding guidance did not independently predict adverse outcomes. However, poor pre-pandemic mental health and low life satisfaction, and frequent loneliness, as well as demographic factors including sex and age, consistently predicted adverse pandemic mental health and wellbeing. Discussion While those who received shielding guidance did on average experience poorer mental health and life satisfaction during the pandemic, this study suggests this largely reflects existing inequalities. Drawing on data throughout the shielding program, it addresses an existing evidence gap. These findings reinforce the importance of addressing existing mental health inequalities in the recovery from the current pandemic and for future preparedness.